Answer:
<h2>h(f(x)) = 2x - 11</h2>
Step-by-step explanation:
f(x) = x - 7
h(x) = 2x + 3
To find h(f(x)) substitute f(x) into h(x) that's replace every x in h(x) by f(x)
That's
h(f(x)) = 2(x - 7) + 3
h(f(x)) = 2x - 14 + 3
We have the final answer as
<h3>h(f(x)) = 2x - 11</h3>
Hope this helps you
Answer: ok
Step-by-step explanation: ok
Answer:
8763
Step-by-step explanation:
Let x represent the number of students the college had last year. Then this year's enrollment is ...
... x - 3%·x = 8500
... x(1 - 0.03) = 8500 . . . . . collect terms
... x = 8500/0.97 ≈ 8762.89 . . . . divide by the coefficient of x
Enrollment last year was about 8763.
_____
Of course, you know 3% = 3/100 = 0.03.
8-4=4
4-(3/4)= 3.25 or 3 1/4
Answer:
u = fv/(v - f)
Step-by-step explanation:
1/f = 1/u + 1/v
1/u = 1/f - 1/v = v/fv - f/fv = (v-f)/fv
1/u = (v-f)/fv
u = fv/(v - f)